Big Data and Public Policy: Can It Succeed Where E‐Participation Has Failed?. Issue 3 (September 2016) - Bright, Jonathan; Margetts, Helen
Abstract : This editorial introduces a special issue resulting from a panel on Internet and policy organized by the Oxford Internet Institute (University of Oxford) at the 2015 International Conference on Public Policy (ICPP) held in Milan. Two main themes emerged from the panel: the challenges of high cost and low participation which many e‐participation initiatives have faced; and the potential Big Data seems to hold for remedying these problems. This introduction briefly presents these themes and links them to the papers in the issue. It argues that Big Data can fix some of the problems typically encountered by e‐participation initiatives: it can offer a solution to the problem of low turnout which is furthermore accessible to government bodies even if they have low levels of financial resources. However, the use of Big Data in this way is also a radically different approach to the problem of involving citizens in policymaking; and the editorial concludes by reflecting on the significance of this for the policymaking process.